Infiltration as a Special Investigative Technique in Combating Cybercrime - Rachida, Henni; Nadia, HAZZAB (Journal of Ecohumanism, 2025)
Infiltration is a new technique introduced by the legislator in the 2006 amendment to the Code of Criminal Procedure. It is used when the necessities of investigation and inquiry require it in the case of serious crimes previously mentioned. The Algerian legislator dedicated Chapter Five of the Code of Criminal Procedure to regulate this measure.According to Article 65 bis 12/1, infiltration is defined as the act of an authorized investigator monitoring individuals suspected of committing a crime, or penetrating a criminal group by deceiving them into believing that he is a partner. Judicial police officers and agents are allowed, for this purpose, to use a false identity and, when necessary, to commit certain crimes without being held criminally liable. This is aimed at monitoring suspects and uncovering their criminal activities while concealing the officer’s true identity.Given the dangerous nature of this procedure, which puts the officers at risk and requires courage, high competence, and precision, the legislator has subjected it to strict legal conditions and controls.